Unhappiness and job finding - Anne C. Gielen; Jan C. van Ours (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
It is puzzling that people feel quite unhappy when they become unemployed, while at the same time active labor market policies are needed to bring unemployed back to work more quickly. Using data from the German Socio-Economic Panel, we investigate whether there is indeed such a puzzle. First, we find that nearly half of the unemployed do not experience a drop in happiness, which might explain why at least some workers need to be activated. In addition to that, we find that even though unemployed who experience a drop in happiness search more actively for a job, it does not speed up their job finding. Apparently, there is no link between unhappiness and the speed of job finding. Hence, there is no contradiction between unemployed being unhappy and the need for activation policies.
Keywords: I31; J64; 330; happiness; unemployment duration; Zufriedenheit; Arbeitslosigkeit; Dauer; Deutschland